Marijuana use experiences and expectancies of urban youth in India - Enub Ali; Ankur Sachdeva; Swatika Gupta; Manoj Kumar; Jai M Singh; Lalit Kardam (Journal of Family Medicine and Primary Care, 2022)
Objective: To gain information on the marijuana experiences and expectancies of youth in an urban Indian area, which may be used for forming the framework for the development of effective primary prevention strategies in the future. Method: This was a cross-sectional study conducted in various colleges of Mumbai; 260 students from three colleges who were above 18 years were selected by systematic random sampling. The participant had to fill a sociodemographic questionnaire and marijuana effect expectancy questionnaire (MEEQ-B) and it was analyzed by using the SPSS software. Results: A significant association was found between negative marijuana expectancies and type of family, with cannabis users and non-users, who want to try cannabis and those who are aware of the legal issues and harmful effects of cannabis. Conclusion: Preventive drug education should begin in early adolescence and should deter or delay drug use through changes in knowledge, attitude, behavior, and expectation. Adolescent drug education must meet the needs of those naive to drugs as well as those experiencing initial drug exposure. This is the first study which highlights the youth experiences and expectancies about marijuana in India.